Investigating the impact of pre-harvesting sprouting on maize hardness using near infrared (NIR) hyperspectral imaging and X-ray micro-computed tomography (μCT) - Mokhoro, Tshepiso (Stellenbosch : Stellenbosch University, 2016)
Thesis (MSc (Food Sc))--Stellenbosch University, 2016.